How Competitive Is Romania’s Agro-Export Sector? Study from 2012 to 2021 - De La Cruz Castellanos, Medalit (2024)
Within the member countries of the European Union, Romania is consolidated as the country with the sixth largest agricultural area and the fifth largest arable area; this natural advantage allows it to be a major agricultural producer and possibly a potential agro-exporter in the world. This research sought to analyse the competitiveness levels of the Romanian agro-export sector through its five most representative products using a competitiveness matrix; as a complement to the analysis, the Revealed Comparative Advantage indicator was used; the information was extracted from the ITC-TradeMap. As general results, Romania evidenced a solid agro-export sector, which manages to compete with the main exporters in the world and even manages to take advantage of different categories of the selected target markets, as is the case of Sunflower Seed.